A rapid CAE-based design method for modular hybrid truss structures. (2019) - Walbrun, Simon; Witzgall, Christian; Wartzack, Sandro
Abstract : The development of hybrid trusses made of carbon-fiber-reinforced plastic struts and aluminum knots is currently not standardized, and there is no overall method for the design, although it has been proven that mass reduction is feasible. This paper introduces a new method for computer-aided engineering based design of hybrid trusses using carbon-fiber-reinforced plastic struts and metal nodes based on a modular system. The method includes all design steps from topology optimization to computer-aided design model generation and offers support to the engineer. The method is discussed in theory. A case study is done with a beam-shaped truss. It shows that if the bisection optimization method is combined with further constraints, it is suitable for selecting the optimum struts from a modular system for the truss. The developed approach is a suitable method for designing hybrid trusses. The basis of the method has been developed and will be further detailed and extended.